Effects of telehealth by allied health professionals and nurses in rural and remote areas: A systematic review and meta-analysis. - Speyer, R.; Denman, D.; Wilkes-Gillan, S.; Chen, Y.; Bogaardt, H.; Kim, J.; Heckathorn, D.; Cordier, Reinie (Stiftelsen Rehabiliteringsinformation, 2017)
OBJECTIVE: To describe telehealth interventions delivered by allied health professionals and nurses in rural and remote areas, and to compare the effects of telehealth interventions with standard face-to-face interventions. DATA SOURCES: CINAHL, Embase, PsycINFO and PubMed databases were searched. The content of relevant journals and published articles were also searched. STUDY SELECTION: Studies examining the effectiveness of allied health and nursing telehealth interventions for rural and remote populations were included in descriptive analyses. Studies comparing telehealth intervention with standard face-to-face interventions grouped by type of intervention approach were used to examine between-groups effect sizes. DATA EXTRACTION: Methodological quality of studies was rated using the QualSyst critical appraisal tool and the National Health and Medical Research Council (NHMRC) Evidence Hierarchy levels. DATA SYNTHESIS: After quality ratings, 43 studies were included. A majority of studies had strong methodological quality. The disciplines of psychology and nursing were represented most frequently, as were studies using a cognitive intervention approach. Meta-analysis results slightly favoured telehealth interventions compared with face-to-face interventions, but did not show significant differences. Interventions using a combined physical and cognitive approach appeared to be more effective. CONCLUSION: Telehealth services may be as effective as face-to-face interventions, which is encouraging given the potential benefits of telehealth in rural and remote areas with regards to healthcare access and time and cost savings.